Assessing purchase factors, purchase intention and word-of-mouth on organic foods purchase decision in Beijing, China - Li, Shimiao (2022)
Under the influences of food safety issue and people’s elevated living standard in China, more and more people are pursuing a healthier diet style. Given such a consumption trend, the organic foods market of developed cities of China had grown rapidly in the last five years. Although, a great number of consumers were enthusiastic about acquiring organic foods, majority of them barely acquired certain knowledge and information related to organic foods. Additionally, it was found that health and hedonic dimensions in food quality were intensively studies with consumers’ purchase intention towards organic foods, whereas convenience and process dimensions have not been fully explored in this situation. Furthermore, food therapy culture as a profound Chinese local culture is worthwhile of being further studied with consumers’ organic food purchase intention within China. More importantly, there was the significant effect of word-of-mouth (WOM) on consumer purchase intention, nevertheless, a little know about its moderating effect on critical gap between purchase intention and purchase decision. As such, this study aimed to examine the key purchase factors, the mediating effect of purchase intention, and the moderating effect of word-of-mouth (WOM). The data were acquired through the purposive sampling method by distributing self-administrative questionnaires among Chinese organic foods consumers in Beijing, China. 405 out of 426 questionnaires were valid to proceed for statistical analysis. All proposed hypotheses were examined via AMOS and SPSS PROCESS regression analysis. The main findings supported significant effects of dimensions in purchase attitude, food quality, perceived behavioral control (PBC), and food therapy culture on purchase intention as well as mediating effect of purchase intention. It is noteworthy that WOM critically addressed the purchase intention and purchase decision gap in studying organic food purchase behavior, which indicated that WOM enables to motivate consumer purchase intention to transit to final purchase decision. ii Besides, a novel insight is conveyed to marketers on how to deepen the relationship between consumer purchase intention and purchase decision towards organic foods by incorporating the vital moderating effect of WOM. Finally, this study made contribution on combining use of theory of reasoned action (TRA), modified theory of planned behavior (TPB), and alphabet theory to redeem the lack of theoretical support occurred in previous studies. While, sample bias, time constraint, single research method are also recognized as the main limitations of the study.